2020
DOI: 10.1016/j.wneu.2020.06.007
|View full text |Cite
|
Sign up to set email alerts
|

COVID 19–Depression and Neurosurgeons

Abstract: and the World Spinal Column Society Executive Board-CONCLUSIONS: Based on the modifiable risk factors of depression in this study, it is recommended that the safety of neurosurgeons be ensured by providing appropriate safety measures for them to regain their confidence and hence reduce the incidence of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 10 publications
1
38
1
5
Order By: Relevance
“…A recent survey involving 375 respondents from 52 countries found that 34% of the respondents felt tense, 32.5% were unhappy, 25% experienced insomnia, almost 20% had headaches, and 5% had suicidal ideation during the pandemic. 17 Of the respondents, 14% were found to have scores consistent with depression on Self-Reporting Questionnaire-20. Various factors identified by this study to be associated with higher risk of depression included those who did not receive guidance about self-protection, those who did not feel safe with provided PPE, and those whose families considered their workplace unsafe.…”
Section: Mental Healthmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent survey involving 375 respondents from 52 countries found that 34% of the respondents felt tense, 32.5% were unhappy, 25% experienced insomnia, almost 20% had headaches, and 5% had suicidal ideation during the pandemic. 17 Of the respondents, 14% were found to have scores consistent with depression on Self-Reporting Questionnaire-20. Various factors identified by this study to be associated with higher risk of depression included those who did not receive guidance about self-protection, those who did not feel safe with provided PPE, and those whose families considered their workplace unsafe.…”
Section: Mental Healthmentioning
confidence: 98%
“… 10 However, there are some major differences in the developed and developing world (e.g., the Indian subcontinent): a large and dense population, limited resources, and already strained health infrastructure. 11 , 12 Recently, a few reports from the developing world 13 , 14 , 15 , 16 , 17 have described the perception of neurosurgeons about the pandemic and changes in neurosurgical practice in the pandemic but there have been none from the Indian subcontinent. Hence, there was a need to understand the effect of the COVID epidemic on neurosurgical practice in the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
“…Our results demonstrate that those who report less availability and/or use of wellness programs at their institution were more likely to demonstrate high depressive symptoms and burn out. This result is echoed in a survey of 375 neurosurgeons taking care of COVID-19 positive patients; Sharif et al found that the likelihood of depression was higher among providers who did not receive guidance about self-protection from their institution(55).…”
mentioning
confidence: 99%
“…Although stress and anxiety during the COVID-19 pandemic is being investigated and dealt with in the general population, 11 in neurosurgeons, [12][13][14] and in some neurosurgical patients, 15,16 to the best of our knowledge there are no reports on anxiety in neurosurgical patients who require nonurgent surgical procedures. The aim of this study was to investigate anxiety in neurosurgical patients undergoing nonurgent surgical procedures in the post-lockdown phase of the COVID-19 pandemic.…”
mentioning
confidence: 99%